Comparative analysis of forced and unforced errors among best eight teams of volleyball of world at Rio Olympics Games - Singh, A.; Pathak, M.; Wani, Z. A.; Haroon, M.; Perray, P.; Bhat, R. A. (International Journal of Innovative Research in Science, Engineering and Technology, 2020)
The mental strength of players and coaches can make the difference when playing in tight games and crucial rallies. To prepare mentally, players must be able to visualize themselves performing a skill correctly, and when a skill is performed incorrectly they must effectively adjust based upon their own observations or feedback from their coach. The players must be able to evaluate the situation in which they find themselves and, if necessary, use a relaxation technique to continue in a positive manner. The players must learn to embrace the very essence of game and relish the opportunity to test their skills and mental toughness against that elusive ball. A forced error is where one player hits a good shot, putting the opponent into a tight spot. For example, carefully angled smash, drop shots, or a sudden change in pace may lead to forced errors. In these situations, the receiver may have to hustle to the ball, become off balance, or set up ball incorrectly in his haste. Since the error was due to that great smash from the opponent, it would be considered a forced error.